New record of monogeneans (Platyhelminthes: Monogenea) infecting some marine fishes from the Peruvian coastal zone - Carvalho-Azevedo, Aline (2021)
A parasitological survey searching monogeneans infesting marine fish was carried out during June 2018 and January 2020 from the coastal zone of Puerto Pizarro, Tumbes (northern Peru) and from the coastal zone of Chorrillos, Lima (central Peru). The gills, skin, nasal cavities, or branchial gill-cover of seven species were sampled. Ten monogenean species assigned to six families and nine genera were identified. The monogeneans Callorhynchocotyle callorhynchi (Manter, 1955); Capsala biparasiticum (Goto, 1894) Price, 1938; Euryhaliotrema sagmatum Kritsky & Boeger, 2002; Listrocephalos kearni Bullard, Payne &Braswell, 2004; Magniexcipula lamothei Bravo-Hollis, 1981; Nasicola klawei (Stunkard, 1962) Yamaguti, 1968; and Pseudorhabdosynochus anulus Violante-Gonzalez & Rojas-Herrera, 2011 are registered for the first time in Peru. While Capsala gregalis (Wagner & Carter, 1967) Chisholm & Whittington, 2007; Heterocotyle margaritae Chero, Cruces, Sáez, Santos & Luque, 2020; and Monocotyle luquei Chero, Cruces, Iannacone, Sanchez, Minaya, Sáez & Alvariño, 2016 have been previously registered in Peruvian waters, however, the region of Tumbes (northern Peru) represent a new locality record for these species.